2021
DOI: 10.3390/e23111478
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of Saturated Vapor over 1-Butyl-3-methylimidazolium Tetrafluoroborate Ionic Liquid: A Multi-Technique Study of the Vaporization Process

Abstract: A multi-technique approach based on Knudsen effusion mass spectrometry, gas phase chromatography, mass spectrometry, NMR and IR spectroscopy, thermal analysis, and quantum-chemical calculations was used to study the evaporation of 1-butyl-3-methylimidazolium tetrafluoroborate (BMImBF4). The saturated vapor over BMImBF4 was shown to have a complex composition which consisted of the neutral ion pairs (NIPs) [BMIm+][BF4−], imidazole-2-ylidene C8N2H14BF3, 1-methylimidazole C4N2H6, 1-butene C4H8, hydrogen fluoride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 56 publications
2
10
0
3
Order By: Relevance
“…This evidence suggests that under effusion conditions, the thermal decomposition of BMImCl is strongly enhanced, whereas the release of gas is greatly reduced under open-surface evaporation. These findings confirm the outcomes of previous works on BMImPF 6 [17] and BMImBF 4 [19]. Moreover, the results of the KEML measurements reported above show that the KEMS-derived pressures, being obtained with an orifice of 1 mm diameter, are much more likely lower than the equilibrium values of processes displayed in Equations ( 4) and (5), which means that performing a thermodynamic analysis on such processes would be improper.…”
Section: Knudsen Effusion Mass Spectrometry (Kems)supporting
confidence: 88%
See 4 more Smart Citations
“…This evidence suggests that under effusion conditions, the thermal decomposition of BMImCl is strongly enhanced, whereas the release of gas is greatly reduced under open-surface evaporation. These findings confirm the outcomes of previous works on BMImPF 6 [17] and BMImBF 4 [19]. Moreover, the results of the KEML measurements reported above show that the KEMS-derived pressures, being obtained with an orifice of 1 mm diameter, are much more likely lower than the equilibrium values of processes displayed in Equations ( 4) and (5), which means that performing a thermodynamic analysis on such processes would be improper.…”
Section: Knudsen Effusion Mass Spectrometry (Kems)supporting
confidence: 88%
“…The occurrence of the thermal decomposition of BMImCl, suggested by the TG experiments, was further investigated by conducting Knudsen effusion mass loss experiments. As mentioned in the introduction, it has been recently shown that the competition between evaporation and decomposition in the BMImPF 6 [17] and BMImBF 4 [19] ILs is significantly affected by the degree of confinement in the sample: the greater the confinement is (e.g., effusion conditions with small orifices), the more thermal decomposition becomes important compared to evaporation, and vice versa. Therefore, under the so-called Langmuir or open-surface conditions, the decomposition is so disfavored that the simple congruent evaporation to NIPs can become the largely dominant process [19].…”
Section: Knudsen Effusion Mass Loss (Keml)mentioning
confidence: 99%
See 3 more Smart Citations